Konsep Islam dalam Mengendalikan PerilakuAntisosial Remaja - Zaenal Abidin (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2008)
family life in modern era indicated erosion of parent's role, responsibility, ond core to educate teenager through their maturity. Therefore, mo/adoptive (ontisociol) teenager od ond behavior that con harm other people. It is because their psychological condition is unstable ond influence of amoral culture, Â cruelty, violence, ond lock of attention ond control of family, school, ond society. If didn't give much core, its con deprive teenager future, so we need urgent alternative solution, namely: return to fundioning family, school ond society to enhance ond educate positive religious values of teenager, involved teenogeron off socio/ religious Â odivity ond toke advocated ond consultative odion on every trouble ond their life problems.